Progress in developing a sweetpotato ontology for breeders - Simon, R.; Hualla, V.; Eyzaguirre, R.; Córdova, R.; Mwanga, Robert O.M.; Rossel, G.; Grüneberg, W.J. (2014)
Crop ontologies have been identified under the Generation Challenge Program and at the International Potato Center (CIP) as a crucial tool for managing and analyzing crop related information. Here we report progress on applying ontological concepts on sweetpotato traits important for breeders and varietal development. We defined a general strategy of identifying important traits based on their re-use in catalogs and experience in usage. A list of about 40 descriptors was identified, including 17 morphological and 22 evaluation traits. Those traits were crosschecked against other crop-ontologies (cassava, barley, maize, solanaceae) on the community site ‘crop ontology’ for consistency. Where appropriate, we annotated linkages. The current draft list of traits is still work-in-progress and subject to further review and refinement. This will include completion of traits, further consistency checks and translation before depositing on the crop-ontology site. The 39 descriptors include morphological (17), agronomical (3), resistance (4), biochemical (11) and post-harvest (4) traits.